2014
DOI: 10.1139/cjp-2013-0385
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering of electrons by calcium atoms

Abstract: The differential, total, and momentum transfer cross sections along with the minima in the differential cross sections (DCSs) and the Sherman function S() for the elastic scattering of electrons by calcium atoms have been calculated. These calculations are done within the framework of complex electron-atom optical potential and relativistic dynamics, in the energy range 1-2000 eV. The results obtained are in good agreement with the available experimental data and are better than the previous calculations in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…This happens also in figure 8(f), where two extremum values of S(θ) lies between +0.991 1 at 126°and −0.997 3 at 127°in the vicinity of 126.5°. These results agree with the work of Hasan et al [48] where they found the variation of S(θ) from +0.54 at 120.5°to −0.75 at 121°for e-Ca scattering at 139.5 eV and from +0.64 at 120.5°to −0.75 at 121°f or 140 eV. This result profoundly reveals the success of OPMD calculations in determining the CM in DCSs for e-Sr scattering.…”
Section: Critical Minima (Cm) In Dcsssupporting
confidence: 92%
“…This happens also in figure 8(f), where two extremum values of S(θ) lies between +0.991 1 at 126°and −0.997 3 at 127°in the vicinity of 126.5°. These results agree with the work of Hasan et al [48] where they found the variation of S(θ) from +0.54 at 120.5°to −0.75 at 121°for e-Ca scattering at 139.5 eV and from +0.64 at 120.5°to −0.75 at 121°f or 140 eV. This result profoundly reveals the success of OPMD calculations in determining the CM in DCSs for e-Sr scattering.…”
Section: Critical Minima (Cm) In Dcsssupporting
confidence: 92%
“…The real part, on the other hand, includes the static [30], the exchange [31] and the polarization [32] potentials. In our calculations of e --atom scattering [33][34][35], we chose a global polarization potential that was a combination of the long-range Buckingham potential and shortrange local-density approximation (LDA) correlation potential. In the present study, instead of Buckingham potential, a parameter free potential due to Sun et al [36] is used as the long-range part of the polarization potential, which allows us to obtain better results of spin-polarization over a wide energy range of 1 eV E 2 keV i   .…”
Section: Introductionmentioning
confidence: 99%
“…see Refs. [15,27,28]), we also employ the DFCP method in our calculations to demonstrate differences between the results from this method and the RCC theory by introducing the CP potential (V cp (r)) in the interaction potential as V (r) = V st (r) + V ex (r) + V cp (r) − ιV ab (r). Here V st (r) and V ex (r) are determined using ρ(r) from the DF method.…”
Section: B Cross-section Calculationsmentioning
confidence: 99%
“…The results are reported for differential cross-sections (DCSs) and integrated cross-sections (ICSs). We compare our results for the free Ca atom with the available experimental data [14] and other reported calculations using the DFCP method [15] in order to gauge accuracies of the results for the confined atom.…”
Section: Introductionmentioning
confidence: 99%